A landlord's certainty : the taxation of property investment - Furfine, Craig (SAGE Business Cases., 2019)
In late 2015, Heather Wilson is finalizing the details on the acquisition of her first investment property, in the Kensington and Chelsea neighborhood of London. As she prepares to become a property investor, Wilson has to learn the details of how property investment is taxed, for only her after-tax returns will add to her wealth over time. As part of her learning, Wilson understands that how she finances the investment will influence the taxes she pays to Her Majesty's Revenue and Customs.